Caffeine increases sprint performance after prolonged exercise in trained cyclists - Dwyer, D.; Ross, R. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Caffeine is a widely used drug which has been shown to have ergogenic effects on sprint performance. Previous research has assessed sprint performance in isolation of prolonged exercise, which is not typical of endurance events that end with a sprint finish. The purpose of the current study was to examine the effects of caffeine on high intensity sprint performance after prolonged exercise. Ten (10) trained cyclists (age, 32.6 ± 9.8 years, mass, 75.40 ± 12.0 kg, peak power, 402.50 ± 54.1 W) participated in a blind cross over design study which involved cycling for 90 minutes at 60% peak power, followed by a sprint to exhaustion at 120% of peak power, with and without caffeine. At 30, 60 and 85 minutes during 90 minutes of cycling and after the sprint, blood lactate concentration and ratings of perceived exertion (RPE) measurements were taken. It was found that caffeine significantly improved sprint performance (p =0.047) after prolonged exercise. There was no difference between blood lactate concentrations at any point during the test. RPE was significantly lower at 30 minutes (p = 0.020) and 60 minutes (p = 0.024) during the caffeine trial, but not at 85 minutes or after the sprint. The results of this study show that caffeine increases cycling sprint performance after prolonged exercise. The ergogenic effect of caffeine may be due to reduced perception of effort, decreased blood lactate concentration or other physiological mechanisms involved in both the central and peripheral nervous systems.